2021
DOI: 10.1186/s12904-020-00704-z
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual care practices in hospices in the Western cape, South Africa: the challenge of diversity

Abstract: Background South Africa is a very diverse middle-income country, still deeply divided by the legacy of its colonial and apartheid past. As part of a larger study, this article explored the experiences and views of representatives of hospices in the Western Cape province of South Africa on the provision of appropriate spiritual care, given local issues and constraints. Methods Two sets of focus group discussions, with 23 hospice participants, were c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…This finding aligns with the results of previous studies that emphasized the significance of spiritual care as an essential aspect of palliative care. It was found that spiritual care can provide a sense of serenity, being present, enabling and alleviating patients' suffering [ 38 , 39 ]. The World Health Organization (WHO) recommends that spiritual care be incorporated as a vital aspect of palliative care for patients, as it can aid in reducing their anxieties and provide comfort [ 29 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with the results of previous studies that emphasized the significance of spiritual care as an essential aspect of palliative care. It was found that spiritual care can provide a sense of serenity, being present, enabling and alleviating patients' suffering [ 38 , 39 ]. The World Health Organization (WHO) recommends that spiritual care be incorporated as a vital aspect of palliative care for patients, as it can aid in reducing their anxieties and provide comfort [ 29 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…• Interviews, face-to-face -Bellamy and Gott [32], Debesay et al [33], de Graaff et al [34,35], Eckemoff et al [37], Henry and Timmins [39], Johnstone et al [40][41][42][43], Khosla et al [44][45][46], Neiman [49], Nielsen et al [50,51], Roider-Schur et al [52], Schrank et al [53], Shahid et al [54], Vincent et al [56], Washington et al [57] • Telephone interviews -Shahid et al [54], Vincent et al [56] • Focus groups -Bellamy and Gott [30], de Voogd et al [36], Khosla et al [44][45][46], Green et al [38], Mahilall et al [47], Milberg et al [48], Neiman [49], Torres et al [55] and Washington et al [57] • Observation -Nielsen et al [50,51] Themes • Communication and connection [33-48, 48, 49, 49, 50, 50, 51, 51-54, 54, 55, 55, 56, 56, 57, 57] • The role of the family in death and dying [33] • The role of education in addressing uncertainty [33, 34, 34, 35, 35, 36, 36, 37, 37, 38, 38, 39, 39, 40, 40, 41, 45, 46, 46, 47, 47, 48, 48, 49, 49-52, 52, 53, 53, 54, 54, 55, 55, 56, 56, 57, 57] • Institutional and societal factors [33-43, 43, 44, 44-46, 46, 47, 47, 48, 48, 49, 49, 50, 50, 51, 51, 52, 52, 53, 53, 54, 54, 55, 55,...…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…One study across 4 papers • Johnstone et al [40,41,41,42,42,43,43,44] • Washington et al [33,57] and Khosla et al [44,45,45,46,46,47] One study across 2 papers • de Graaff et al [34,35,35,36] • Roider-Schur et al [52,53] Country of origin • Austria [52,53] • Australia [38,[40][41][42][43] • Canada [50,51,56] • Ireland [39] • Netherlands [34][35][36] • New Zealand [30] • Norway [33] • Sweden [48,55] • United States [37, 44-46, 49, 57] • South Africa [47].…”
Section: Papersmentioning
confidence: 99%
“…At SLCH, the spiritual care services are offered predominantly by volunteers, with three being paid staff, of whom two are part-time employees. Spiritual care services are offered by very few organisations in SA, with SLCH having one of the largest cohorts of spiritual care workers in SA (Mahilall and Swartz, 2021b ).…”
Section: Methodsmentioning
confidence: 99%